2016
DOI: 10.1186/s41118-016-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial clustering and risk factors of infant mortality: district-level assessment of high-focus states in India

Abstract: The study analyzes the spatial clustering and risk factors of infant mortality across high-focus states of India, using the Annual Health Survey (2010-2011), Census of India (2011), and District Level Household and Facility Survey-3 (2007-2008. Research has found substantial spatial autocorrelation across the districts and identified the "hot spots" characterized by higher infant mortality rate (IMR) in the districts of the central region (Uttar Pradesh and Madhya Pradesh) of India. This study has considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
(22 reference statements)
3
24
0
Order By: Relevance
“…The similar spatial clustering in childhood malnutrition was observed in a recent study. 34 Earlier studies [34][35][36][37] showed clustering of infant and child mortality and its contextual correlates. In the present paper, bivariate LISA maps highlight a total of 159 hot spots districts mostly from the central and eastern part of India.…”
Section: Discussionmentioning
confidence: 99%
“…The similar spatial clustering in childhood malnutrition was observed in a recent study. 34 Earlier studies [34][35][36][37] showed clustering of infant and child mortality and its contextual correlates. In the present paper, bivariate LISA maps highlight a total of 159 hot spots districts mostly from the central and eastern part of India.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a great deal of information on socioeconomic and geographical disparity in neonatal, infant, and UFM in recent years [ 2 – 12 ]. Only a few studies, however, have examined that disparity at below the Indian state level [ 4 , 13 15 ]. Ram and colleagues [ 13 ] applied the state and district mortality-rate pattern, derived from a few nationally representative surveys, to the 2012 UN sex-specific birth and mortality totals; the researchers indirectly calculated that only 37% of 597 districts were on track to achieve Millennium Development Goal (MDG) number 4 of 38 deaths per 1000 live births among the under-fives by 2015, and only around another 37% after 2020.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that more districts lagged behind the respective goal for NMR than for the U5MR. Gupta et al [ 4 ] examined the spatial clustering and risk factors of infant mortality rate (IMR) across nine high focused states of India. The nine high focused states are Assam, Bihar, Chhattisgarh, Jharkhand, Madhya Pradesh, Odisha, Rajasthan, Uttarakhand and Uttar Pradesh.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol trade is also an important source of revenue in India, where non-commercial production of alcohol is the primary livelihood of women from Assam and Sikkim (Chakrabarti et al, 2012). Smoking and drinking alcohol is still a taboo among women in certain parts of the country but chewing tobacco is common among women due to their acceptability in society, ease of availability and inexpensiveness (Gupta et al,2016;Sauvaget et al, 2008). Thankappan & Thresia, (2007) had shown that ban on smoking in the public places of India had resulted in an increment in smokeless tobacco consumption in India.…”
Section: Introductionmentioning
confidence: 99%